Biomarkers of Inflammation and Progression During Immunotherapy in Patients With Metastatic Renal Cell Carcinoma - Spisarova, Martina; Melichar, Bohuslav; Juranova, Jarmila; Zemankova, Anezka; Adam, Tomas; Matousova, Katerina; Javorska, Lenka; Krcmova, Lenka Kujovska; Turonova, Dorota; Studentova, Hana (In vivo (Athens, Greece), 2023)
BACKGROUND/AIM: Biomarkers that would identify patients unlikely to respond to immunotherapy with immune checkpoint inhibitors (ICIs) remain an unmet medical need. PATIENTS AND METHODS: In the present study, we have retrospectively evaluated the association between biomarkers of immune activation and outcome in metastatic renal cell carcinoma (mRCC) patients treated with ICIs. The laboratory and clinical data of 79 consecutive patients with histologically confirmed mRCC treated with ICI-based immunotherapy have been analyzed. RESULTS: Patients who progressed or died at 4 months had higher prognostic score, higher serum C-reactive protein (CRP) and neopterin, and urinary neopterin, and lower serum albumin and hemoglobin concentration. CONCLUSION: Biomarkers of activation of immune response, in particular serum neopterin/creatinine ratio, are associated with outcome in mRCC patients treated with ICI immunotherapy.
Keywords: nádory ledvin; karcinom z renálních buněk; Carcinoma, Renal Cell; retrospektivní studie; peripheral blood cell count; Inflammation; Humans; biologické markery; lidé; neopterin; imunoterapie; Retrospective Studies; Kidney Neoplasms; Biomarkers; Immunotherapy; zánět; Neopterin; renal cell carcinoma